Height at 2 and 5 years of age in children born very preterm: the EPIPAGE study. Issue 5 (17th January 2011) - Pierrat, V; Marchand-Martin, L; Guemas, I; Matis, J; Burguet, A; Picaud, J C; Fresson, J; Alberge, C; Marret, S; Roze, J C; Kaminski, M; Larroque, B; et al.
Abstract : Objectives: To evaluate growth for children born very preterm with particular focus on those born small-for-gestational age (SGA) or with ex utero growth restraint (GR), and to identify risk factors for short stature at 5 years of age. Study design: Population-based study of children born at less than 33 completed weeks of gestation (Étude Epidémiologique sur les Petits Ages Gestationnels (EPIPAGE)). Short stature was defined as height <−2SD on WHO growth curves. Ex utero GR was considered to have occurred in children with appropriate size for gestational age at birth and with a height and/or weight below −2SD at 2 years of corrected age. Logistic regression models were used to test associations between risk factors and short stature. Results: The authors measured height at 5 years of age for 1597 of 2193 children (73%), 5.6% (95% CI 4.6 to 6.9) of whom were diagnosed as having a short stature. Height was measured at 2 and 5 years of age in 1417 children. Among these, 24% of those born SGA and 36% of those with ex utero GR (p=0.002) had a short stature at 5 years. Predictors of short stature were SGA or birth length <−2SD, maternal height ≤ 160 cm, gestational age <29 weeks and systemic corticosteroids. Breastfeeding at discharge decreased the risk of short stature. Conclusions: Short stature at 5 years of age is common in children born preterm. The highest incidence was observed in the group with ex utero GR. Systemic steroids have a long-term impact on growth and should be used with caution. Breastfeeding at discharge appeared to be protective.